ANALISIS KARAKTERISTIK PETANI KENTANG TERHADAP TINGKAT PRODUKSI KENTANG (Solanum sp) KECAMATAN JAGONG JEGET KABUPATEN ACEH TENGAH - Fitri, Ilma 23 (Biram Samtani Sains, 2024)
ABSTRACT Potatoes are a commodity that can be counted on by farmers. Potato farming plays a role in the obstacles that farmers often face in increasing potato production, namely that there are too many costs incurred in producing potato crops, while the price of the research objective is to analyze and determine the relationship between the characteristics of potato farmers and the production of potato farming in Jagong Jeget District, Central Aceh Regency. Based on age, the results of the analysis using chi-square. The significance value obtained is 0.00, it can be concluded that H0 is rejected and H1 is accepted, meaning there is a relationship between farmer age and potato production. Based on education, the results of the analysis using chi-square. The significance value obtained is 0.97, it can be concluded that H1 is rejected and H0 is accepted, meaning that there is no relationship between farmer education and potato production. Based on the number of dependents, the results of analysis using chi-square. The significance value obtained is 0.21, it can be concluded that H1 is rejected and H0 is accepted, meaning that there is no relationship between the number of farmers' dependents and potato production. Based on the length of farming, the results of the analysis use chi-square. The significance value obtained is 0.6, it can be concluded that H0 is accepted and H1 is rejected, meaning there is no relationship between the length of time a farmer has been farming and potato production. Based on the land area, the results of the analysis use chi-square. The significance value obtained is 0.00, it can be concluded that H0 is rejected and H1 is accepted, meaning there is a relationship between the amount of land cultivated by farmers and potato production. Key: Analysis, characteristics, farmers, potatoes, relationships.